Comparison Of Murabahah And Musyarakah Mutanaqisah Financing Management Strategies - Ramadani, Uci; Izmuddin, Iiz (LPPM ISNJ Bengkalis, 2024)
This research analyses the comparison of murabaha and musyarakah mutanaqisah financing management strategies. This research is field research with data sources coming from primary and secondary data through observation, interviews, questionnaires, documentation and focus group discussions (FGD). Data analysis uses a mixed method approach, quantitatively and qualitatively using IFAS, EFAS matrices, SWOT diagrams and SWOT matrices. This research found advantages and disadvantages to murabaha and musyarakah mutanaqisah financing. Murabaha financing is quite familiar compared to musyarakah mutanaqisah financing and is currently in an aggressive strategic position with a strengths-opportunity score of 3.0. This position is very profitable for bank nagari syariah Bukittinggi. For musyarakah mutanaqisah financing, it is currently also in a favourable position. However, under Murabaha financing with a total strengths-opportunity score of 1.15, this position is still profitable for bank nagari syariah Bukittinggi. However, the weakness of musyarakah mutanaqisah means that financing distribution could be more optimal. Mutanaqisah musyarakah financing has incredible strengths and opportunities if it maximises its strategy. This research can complement existing theory and become a reference for bank nagari syariah Bukittinggi in improving its financing management strategy to support financing growth and meet community needs.